Pengelolaan Wisata Daerah Untuk Meningkatkan Pendapatan Asli Daerah (Studi Pada Pengelolaan Wisata Unggulan Kayangan Api Kabupaten Bojonegoro) - Dewi, Tri Wulan Suryaning; Ma’ruf, Muhammad Farid (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Tourism is a strategic sector in driving regional economic growth through increasing local revenue, job creation, and community empowerment. One of the leading destinations in Bojonegoro Regency is Kayangan Api, famous for its unique eternal fire natural phenomenon and high historical and cultural value. However, the development of this area still faces challenges such as limited accessibility, inadequate supporting facilities, and minimal additional attractions. This study aims to describe the Kayangan Api tourism development strategy to increase its contribution to local revenue, using Cooper's 4A theory (1995): attraction, accessibility, amenity, and ancillary services. The study was conducted qualitatively descriptively through interviews with the Tourism Office, business actors, and visitors, as well as observation and documentation. The results of the study showed that the main attraction of Kayangan Api is the eternal fire which has geological and spiritual value, reinforced by Air Blukutuk, the Love Tree, and the legend of Empu Kriyokusumo. In terms of accessibility, the road to the location has been repaired, but public transportation is not yet available. Public facilities such as toilets and souvenir centers are already available, but interactive and educational rides are still lacking. Meanwhile, additional service support is still limited and community participation is not optimal. This study concludes that there is an imbalance between tourism potential and management. Therefore, an integrated development strategy is needed, such as the addition of educational attractions, public transportation, and community involvement to increase the competitiveness and contribution of Kayangan Api to the original income of the Bojonegoro region